2011
DOI: 10.1016/j.cyto.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the concentration and correlation of cervical immune markers among HPV positive and negative perimenopausal women

Abstract: Introduction Women ≥45 years of age with persistent HPV infections have distinct peripheral circulating immune profiles. Few studies have comprehensively evaluated the cervical immunologic microenvironment in HPV-positive and HPV-negative perimenopausal women. Methods We collected cervical secretion specimens from 34 high risk HPV (HR-HPV) positive and 44 HR-HPV negative women enrolled in an ongoing prospective cohort assessing the natural history of HPV across the menopausal transition. We used these specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 27 publications
1
41
2
2
Order By: Relevance
“…Recently, increased IL-17 production has been associated with persistent HPV16/18 infection and cervical epithelial neoplasia and transformation (15, 16). However, the function of IL-17 in viral persistence and premalignant epithelial disease is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increased IL-17 production has been associated with persistent HPV16/18 infection and cervical epithelial neoplasia and transformation (15, 16). However, the function of IL-17 in viral persistence and premalignant epithelial disease is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the authors have evaluated immune markers that were locally secreted in the cervix, tissue-based immune markers or immune response by patient-derived peripheral blood mononuclear cells (PBMCs) [27][28][29][30]. However, data concerning infection-related immune response in either plasma or serum is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven cervical secretion studies included in this review, two collected cervical secretions through cervicovaginal lavage (Tjiong, van der Vange et al 2001;Guha and Chatterjee 2009), four used Weck-cel® (Crowley-Nowick, Ellenberg et al 2000; or Merocel® (Lieberman, Moscicki et al 2008;Marks, Viscidi et al 2011) ophthalmic sponges, and one used cytobrush sample suspensions (Scott, Stites et al 1999). Cervicovaginal lavages may not be specific enough to the cervix and may overly dilute the specimen.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Currently, seven studies that met our inclusion criteria have measured immune responses in cervical secretions (Table 2). Unlike the studies of circulating cytokines above, most of these studies have tested for a broad range of HPV types, although one (Guha and Chatterjee, 2009) only tested for carcinogenic HPV types using the Hybrid Capture 2 assay, and another only analyzed results for women with carcinogenic HPV infection compared to women without carcinogenic HPV infection (Marks, Viscidi et al 2011). Scott et al (Scott, Stites et al 1999) found no statistical differences in IL-10 and IL-12 concentrations by HPV-positivity versus HPV-negativity in women selected from a population-based cohort study in Guanacaste, Costa Rica, after adjusting for stage of menstrual cycle, recent oral contraceptive use secretion volume, and pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation